Surface Modification of Monolayer MoS2 by Baking for Biomedical Applications - Wang, Yan; Ma, Yuanjun; Shi, Jinping; Yan, Xiangyu; Luo, Jun; Zhu, Huilong; Jia, Kunpeng; Li, Juan; Zhang, Can Yang (Frontiers in Chemistry, 2020)
MoS2, a transition metal dichalcogenide (TMDC) material, possesses a great potential in biomedical applications such as chemical/biological sensing, drug/gene delivery, bioimaging, phototherapy, and so on. Particularly, monolayer MoS2 has more extensive applications due to its fantastic physical and chemical properties such as ultra-high surface area, easy modified and high biodegradability. It is of great significance to prepare advanced monolayer MoS2 with enhanced energy exchange efficiency (EEE) for development of MoS2-based nanodevices and therapeutic strategies. In this work, monolayer MoS2 film was firstly synthesized through chemical vapour deposition (CVD) method, and the surface of MoS2 was further modified via baking process to develop p-type doping of monolayer MoS2 with high EEE. After baking process, the surface of monolayer MoS2 was transferred to p-type doping, followed by confirming by X-ray photoelectron spectroscopy (XPS) and Raman spectra analysis. The morphology, surface roughness and layer thickness of monolayer MoS2 before and after baking were thoroughly investigated using atomic force microscopy (AFM). The results showed that the surface roughness and layer thickness of monolayer MoS2 modified by baking were obviously increased in comparison to those of MoS2 without baking, indicating the higher energy conversion efficiency of p-type doping. Moreover, photoluminescence (PL) spectrum study revealed that p-type doping of monolayer MoS2 displayed much stronger photoluminescence ability which was taken as an evidence of higher photothermal conversion efficiency. This study not only developed a novel MoS2 with high EEE for future biomedical application but also demonstrated that baking process is a promising way to modify the surface of monolayer MoS2.